The Effects of Climate Change on Coastal Erosion in West Africa - World Bank Group (World Bank, Washington, DC, 2016)
The effects of climate change, from changing precipitation patterns to rising seas, will exacerbate the coastal erosion already affecting West Africa, increasing the exposure and vulnerability of the people and assets located there. Given the importance of the coastal zone to the region as a whole, it is critical that policy makers consider the effects of future climate change in the decisions they make today. Regional cooperation is challenging, but it has been successful in many places, particularly where the issue addressed presented an existential challenge to the coun¬tries affected. Efforts to build trust and coordinate efforts will help policy makers protect the lives and livelihoods of the people in the region and allow their countries to build on the development gains made in recent years rather than see them rolled back as a result of climate change.